Synergistic action of Thyroxine & Vitamin B12 on Electrophysiological Changes in sensory functions of Median Nerve in Newly Diagnosed Hypothyroid Female (Journal of Dhaka National Medical College & Hospital, 2021)
Background: Synergistic action of thyroxine & vitamin B12 can improve the electrophysiological status of sensory function of median nerve in newly diagnosed hypothyroid patients. Objectives: To observe the synergistic action of thyroxine & vitamin B12 on electrophysiological changes in sensory function of median nerve of newly diagnosed hypothyroid female.Materials and Methods: This prospective interventional study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC) between July' 2015 to June' 2016 on 40 newly diagnosed hypothyroid female patients. Among them, 20 patients received only thyroxine termed as HT-T4 and another 20 patients received combined therapy of thyroxine with vitamin B12 termed as HT-C for 90 consecutive days. Nerve conduction parameters of sensory functions of median nerve were studied to observe the electrophysiological status and vitamin B12 level was also estimated to observe its level by using standard method. The statistical analysis was done by ANOVA test, paired, independent sample 't' test and Chi-square (χ2) test.Results: In this study, latency was significantly decreased, amplitude and NCV were significantly increased in sensory functions of median nerve of hypothyroid patients after 90 days supplementation of combined therapy of thyroxine with vitamin B12 in comparison to those of their pre-supplemented state and also to those of patients with only thyroxine treatment.Conclusion: The present study revealed the combination of thyroxine with vitamin B12 can reduce the symptoms of hypothyroid and accelerate the nerve conduction velocity of sensory functions of median nerve more efficiently than the treatment with thyroxine alone.J. Dhaka National Med. Coll. Hos. 2021; 27 (01): 07-11